2015
DOI: 10.1002/ca.22502
|View full text |Cite
|
Sign up to set email alerts
|

Terminal innervation of female genitalia, cutaneous sensory receptors of the epithelium of the labia minora

Abstract: FNEs, Meissner's corpuscles and Pacinian corpuscles are present in the female labia minora and exhibit characteristic staining patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Malinovský et al described several types of encapsulated and non‐capsulated corpuscles in the human vulva, considering only a minority of the non‐capsulated corpuscles as genuinely reminiscent of cutaneous Meissner corpuscles. Nevertheless, Schober et al failed to identify such diverse types of corpuscles, but also identified pseudo‐Meissner corpuscles . Our present results basically agree with previous studies reporting the occurrence of different morphotypes of sensory corpuscles, including non‐capsulated Meissner‐like and partially‐capsulated glomerular corpuscles, in human female genital skin .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Malinovský et al described several types of encapsulated and non‐capsulated corpuscles in the human vulva, considering only a minority of the non‐capsulated corpuscles as genuinely reminiscent of cutaneous Meissner corpuscles. Nevertheless, Schober et al failed to identify such diverse types of corpuscles, but also identified pseudo‐Meissner corpuscles . Our present results basically agree with previous studies reporting the occurrence of different morphotypes of sensory corpuscles, including non‐capsulated Meissner‐like and partially‐capsulated glomerular corpuscles, in human female genital skin .…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, Schober et al failed to identify such diverse types of corpuscles, but also identified pseudo‐Meissner corpuscles . Our present results basically agree with previous studies reporting the occurrence of different morphotypes of sensory corpuscles, including non‐capsulated Meissner‐like and partially‐capsulated glomerular corpuscles, in human female genital skin . Nevertheless, the large size, sometimes angulated morphology and irregular intracorpuscular axonal course in the Meissner‐like corpuscles suggests that they are influenced by the hamartomatous lesion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Currently, there are no effective treatment options specifically targeting the genital, rather than psychological, component of female sexual arousal . In part, this is due to the challenge of studying the mechanisms of the physiological components of female arousal, an area of research that is still developing . A treatment for genital arousal dysfunction may also affect other components of sexual dysfunction, and thus would have wide applicability across FSD subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…The nerve branches to the vulva also possess A delta and C fibers that serve as nociceptors (Steege and Zolnoun, ). The labia minora also possesses some terminal sensory fibers that might play a role in pain perception (Schober et al, ).…”
Section: Relevant Anatomy and Neurophysiologymentioning
confidence: 99%